Low MFN2 expression related to ageing in granulosa cells is associated with assisted reproductive technology outcome. Issue 2 (February 2019) - Wang, Lingjuan; Song, Su; Liu, Xuemei; Zhang, Mengdi; Xiang, Wenpei
Abstract: Research question: Is low MFN2 expression associated with ageing in granulosa cells as well as assisted reproductive technology (ART) outcome, and what is the underlying mechanism of action of MFN2? Design: In a prospective study, fresh granulosa cells were obtained from 161 women aged 20–40 years who underwent IVF with embryo transfer and who were divided into two groups: the diminished ovarian reserve (DOR) group ( n  = 51) and the control group ( n  = 110). Patient characteristics including age, infertility duration, body mass index, FSH, anti-Müllerian hormone (AMH), antral follicle count (AFC) and husband's semen parameters and granulosa cell MFN2 expression levels, cell apoptosis, mitochondrial membrane potential (ΔΨm) and ATP levels were analysed. Results: There were no significant differences between the DOR and control groups in terms of age, infertility duration and husband'' semen parameters; however, significant ( P < 0.05) changes were found between the two groups in FSH, AMH and AFC levels. MFN2 expression was remarkably lower in granulosa cells from the DOR group and decreased in both groups as age increased. Furthermore, among young patients, MFN2 levels significantly increased in patients with pregnancy. MFN2 protein levels and cell apoptosis were lower in the MFN2 knockdown (MFN2-siRNA) group than in the control (Cy3-siRNA) group. ΔΨm and ATP levels were reduced in the MFN2-siRNA group compared with the Cy3-siRNA group. Conclusions: Low MFN2 expression levels in granulosa cells were related to ageing, which may be involved in the clinical outcome of ART by promoting cell apoptosis and affecting mitochondrial function.